Online cardiac output estimation during transvalvular left ventricular assistance. (April 2019) - Rüschen, Daniel; Rimke, Miriam; Gesenhues, Jonas; Leonhardt, Steffen; Walter, Marian
Highlights: A novel method for estimation of cardiac output using optical pressure sensors mounted on a VAD is introduced. An extended Kalman filter for state and parameter estimation of a simple cardiovascular system model is proposed. The cardiac output estimator is tested in a hybrid mock circulatory loop and in an animal study with two sheep. The estimation errors are in the same range as the accuracy of the gold standard in research for invasive blood flow measurement. Abstract: Background and objectives: Sufficient cardiac output is one of the main goals of ventricular assist device therapy. To date, there is no adequate method to estimate the combined amount of blood the native heart and a continuous-flow assist device pump through the circulatory system. This paper presents an approach to estimate total cardiac output based on the signals provided by optical pressure sensors mounted on the inlet and outlet of an Abiomed Impella CP pump. Methods: Two Kalman filters were used in parallel for joint estimation of the aortic flow rate and the hydraulic resistance of the aortic valve. The filters utilized a third order nonlinear state-space representation of the cardiovascular system with two nominal parameter sets, one for ovine and another for human subjects. The accuracy of the estimated cardiac output has been investigated in a hybrid mock circulatory loop and an animal study involving two sheep with experimentally induced acute ischaemic heart disease supported by a transvalvular left ventricular assist device. Results: The in vitro accuracy of the cardiac output estimation is ±3.64%. In an ovine model, the comparison of the estimated cardiac output with an ultrasonic flow measurement in the pulmonary artery showed 95% limits of agreement of −0.004 ± 0.897 L min −1 . The estimation errors were comparable to the accuracy of the measurement (±10%), which is the gold standard in research for invasive blood flow diagnostics. Conclusions: The online estimation of total cardiac output may give the treating physician a direct and physiologically meaningful feedback on the pump speed setting. One promising possible application of our method is physiological control, where the cardiac output can be used as the control variable for closed-loop ventricular assist device therapy.